Synergism of Zinc Oxide Quantum Dots with Antifungal Drugs: Potential Approach for Combination Therapy against Drug Resistant Candida albicans - Chand, Preeti; Kumari, Sangeeta; Mondal, Neelima; Singh, Surinder P.; Prasad, Tulika (Frontiers in Nanotechnology, 2021)
Candidiasis caused by Candida albicans is one of the most common microbial infections. Azoles, polyenes, allylamines and echinocandins are classes of antifungals used for treating Candida infections. Standard drug doses often become ineffective due to emergence of multidrug resistance (MDR), This leads to use of higher drug doses for prolonged duration, resulting in severe toxicity (nephrotoxicity and liver damage). However, combination therapy using very low concentrations of two or more antifungal agents could lower such toxicity and limit evolution of drug resistance. Herein, 4-6 nm Zinc Oxide Quantum Dots (ZnO QDs) were synthesized and in vitro antifungal activities assessed against drug susceptible (G1, F1 and Gu4) and resistant (G5, F5 and Gu5) isolates of C. albicans. In broth microdilution assay, ZnO QDs exhibited dose dependent growth inhibition between 0 – 200 µg/ ml and almost 90 % growth was inhibited in all Candida strains at 200 µg/ ml ZnO QDs. Synergy between ZnO QDs and antifungal drugs at sub-inhibitory concentrations was assessed by Checkerboard analysis and expressed in terms of Fractional inhibitory concentration (FIC) index. Results demonstrated that the potency of combinations of ZnO QDs with antifungal drugs even at very low concentrations of each was higher than their individual activities against the fungal isolates. FIC index was found to be less than 0.5 for all combinations in Checkerboard assay, which confirmed synergism between sub-inhibitory concentrations of both ZnO QDs (25 µg/ ml) and individual antifungal drugs. Synergism was confirmed by Spot assay where cell viabilities of Candida strains were significantly reduced in all combinations, which was clearly evident from disappearance of fungal cells on agar plates containing antifungal combinations. For safer clinical use, the in vitro cytotoxic activity of ZnO QDs was assessed against HeLa cell line and it was found that ZnO QDs were non-toxic at 25 µg/ ml. Results suggested that the combination of ZnO QDs with drugs potentiate antimicrobial activity through multi-targeted action. ZnO QDs could therefore, offer versatile alternative in combination therapy against MDR fungal pathogens, wherein lowering of drug concentrations can reduce toxicity and their multitargeted action can limit evolution of fungal drug resistance.